Fifth wave of COVID-19 and use of masks in open and enclosed spaces - Fuertes-Bucheli, José Fernando; Peláez-Martínez, Juan David; Martínez-Niño, María del Mar; Aguilar-Gonzalez, Ana María; Dorris, Madeline; Ferro, Beatriz E.; Pacheco, Robinson (Universidad y Salud, 2022)
Introduction: The management of the COVID-19 pandemic demands adaptations to each epidemiological moment. Objective: To analyze the epidemiological behavior of COVID-19 in Cali (Colombia) after removing the mandatory use of mask in open and enclosed spaces between March 1st to July 11th of 2022. Materials and methods: A descriptive observational study of COVID-19 cases and incidence proportion (IP) for 7 days, with two temporary milestones: desisting from mandatory mask use in open and enclosed spaces, using data published by the Instituto Nacional de Salud. The temporary trend was evaluated with the non-parametric Mann-Kendall test. Results: Differences between the first and second milestones were shown: 922 cases in 75 days versus 12,037 in 59 days; Tau=-0.22 versus 0.57, S=-608 versus 968, Var(S)=47,574.66 versus 233,280.66; Sen’s slope=-0.10 (CI95%: -0.18 and -0.03) versus 7.39 (CI95%: 5.23 and 8.88). After the second milestone, the IP increased with a positive trend (S=23, p=0.006). Conclusions: The significant increase in COVID-19 cases and in IP coincided with removing the mandatory use of mask mandates in enclosed spaces. This reinforces the recommendations to use masks in enclosed spaces, strengthen the management of the infodemic, promote vaccination and increase natural ventilation.